2020
DOI: 10.1111/cob.12395
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioural strategies employed to overcome “lapses” and prevent “relapse” among weight‐loss maintainers and regainers: A qualitative study

Abstract: Summary While many behavioural weight management programmes are effective in the short‐term, post‐programme weight regain is common. Overcoming “lapses” and preventing “relapse” has been highlighted as important in weight‐loss maintenance, but little is known on how this is achieved. This study aimed to compare the cognitive and behavioural strategies employed to overcome “lapses” and prevent “relapse” by people who had regained weight or maintained weight‐loss after participating in a weight management progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…In addition, we conducted primary research to fill several evidence gaps that we identified. Full reports of each of these primary studies have been published elsewhere [ 9 , 28 ]. The key methods and findings relevant to the intervention development are briefly described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we conducted primary research to fill several evidence gaps that we identified. Full reports of each of these primary studies have been published elsewhere [ 9 , 28 ]. The key methods and findings relevant to the intervention development are briefly described below.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted semistructured interviews [ 28 ] with 26 participants (15/26, 58% female) from the Weight loss program Referrals for Adults in Primary care (WRAP) trial [ 8 ]. Participants randomized to the intervention arms of the WRAP trial (referral to 12 or 52 weeks of a commercial weight loss program) and who had lost ≥5% baseline weight during the active intervention (year 0-1) were recruited at the 5-year follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The most effective strategies involved avoidance of the foodprovisioning environment, for example, by shopping less often 46 or never entering certain supermarket aisles. 41,46,48 In some cases, people avoided certain types of food, such as less nutritious snacks 36 or delivery food. 39 People have more confidence in employing effective strategies after workshop-style education that includes a nutrition expert and some form of ongoing support…”
Section: Constant Effort Is Required To Navigate the Food Environmentmentioning
confidence: 99%
“…31,38,53 Participants across various studies saw social situations as one of the strongest challenges, as going out acted as a "trigger" for consuming HFSS food. 39,41,43,49 This was the case even outside of restaurants and cafes, as friends and colleagues were likely to bring less nutritious foods to social occasions. 53,54 How others expect someone to engage with the food environment can present a challenge to weight management strategies People's social networks often included people who ate the same way and disliked any change in one person's eating practices.…”
Section: When Social Situations Intersect With the Food Environment Weight Management Is Particularly Challengingmentioning
confidence: 99%